2021
DOI: 10.29244/jsdh.7.1.25-35
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Tumbuhan Penghasil Polen dari Madu Lebah Tanpa Sengat di Belitung

Abstract: Stingless bees forage to the flower for nectar and at the same time, pollen also trapped in the body hairs of the bees. Mostly pollen was concentrated into the pollen basket and transferred to the pollen and honey pot in the stingless bee nest. Pollen is male gametophytes of seed plants which have various of shapes, sizes, and ornamentations. This palynology study was aimed to identify the plants of pollen source that were found in honey of stingless bee Heterotrigona itama and Tetragonula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…Melissopalynology is a method used to identify bee food sources through pollen identification in bee bread and pollen contaminants in honey. The pollen forms align with the findings of studies by [17]; [18]; [19].…”
Section: The Percentage Of Pollen In Bee Bread and Honeysupporting
confidence: 86%
“…Melissopalynology is a method used to identify bee food sources through pollen identification in bee bread and pollen contaminants in honey. The pollen forms align with the findings of studies by [17]; [18]; [19].…”
Section: The Percentage Of Pollen In Bee Bread and Honeysupporting
confidence: 86%
“…In the case of plants with flowers that appear throughout the year, such Coral vine A. leptopus, shorter distances will allow stingless bees to get food quickly. It was under research [14], which reported that the body size of the stingless bee was small because its ability to fly was not too far from the nest. Pratama et al [15] reported that Trigona stingless bees look for food sources at a maximum distance of 497m.…”
Section: The Shape Of Bee Boxes and Its Locationmentioning
confidence: 99%
“…Tanaman herba seperti nanas, maman ungu, rumput ekor kucing, kumpai segitiga, rumput para, dan bandotan, mudah ditemukan, pertumbuhannya cepat, dan sebagian besar dapat berbunga sepanjang tahun dan tidak dipengaruhi oleh iklim (Rismayanti et al, 2015). Diversifikasi jenis tanaman potensial untuk sumber pakan lebah madu sangat penting untuk pengembangan budi daya lebah madu karena dapat memengaruhi perkembangan lebah serta produksi madu, propolis dan bee bread (Agussalim et al, 2017;Priambudi et al, 2021;Wahyuningsih et al, 2021). Resin diperlukan oleh lebah kelulut untuk membuat sarang, melindungi sarang dari bakteri dan jamur serta menghasilkan produk berupa propolis (Bankova et al, 2002;Hasan et al, 2019;Ivančajić et al, 2010).…”
Section: Pembahasanunclassified